Life-Threatening Postpneumonectomy Syndrome Complicated with Right Aortic Arch after Left Pneumonectomy - Takahiro Karasaki; Makoto Tanaka (Case Reports in Surgery)
A 54-year-old man with right aortic arch underwent left lower lobectomy and lingular segmentectomy, followed by complete pneumonectomy, for refractory nontuberculous mycobacterial infection. Three months after the pneumonectomy, he developed acute respiratory distress. Computed tomography showed an excessive mediastinal shift with an extremely narrowed bronchus intermedius and right lower bronchus compressed between the right pulmonary artery and the right descending aorta. Soon after the nearly obstructed bronchus intermedius was observed by bronchoscopy, he began to exhibit frequent hypoxic attacks, perhaps due to mucosal edema. Emergent surgical repositioning of the mediastinum and decompression of the bronchus was indicated. After complete adhesiolysis of the left thoracic cavity was performed, to maintain the proper mediastinal position, considering the emergent setting, an open wound thoracostomy was created and piles of gauze were inserted, mildly compressing the heart and the mediastinum to the right side. Thoracoplasty was performed three months later, and he was eventually discharged without any dressings needed. Mediastinal repositioning under thoracostomy should be avoided in elective cases because of its extremely high invasiveness. However, in the case of life-threatening postpneumonectomy syndrome in an emergent setting, mediastinal repositioning under thoracostomy may be an option to save life, which every thoracic surgeon could attempt.